Cardiomyocyte Contractile Force Changes in Response to Chemical Environments - You, Jin; Moon, Hyowon; Lee, Boo Yong; Jin, Ju Young; Hwang, Yu-Shik; Suh, Jun-Kyo Francis; Kim, Jinseok; Park, Jungyul; Chang, Zi Eun (2014 9TH IEEE INTERNATIONAL CONFERENCE ON NANO/MICRO ENGINEERED AND MOLECULAR SYSTEMS (NEMS), 2014)
In this study, we demonstrate that drug treatments change cardiomyocyte contractile force in vitro. Contractile force was determined by bending deflection of the cantilever end. We quantified the effect of Digoxin, Isoproterenol, and BayK8644, drugs that increase contractile force, on cardiomyocyte contractile forces when grown on the grooved cantilever. We also investigated the effect of Verapamil, which decreases contractile force. We applied Digoxin, Isoproterenol, and BayK8644 on day 8, and Verapamil on day 5. Digoxin, Isoproterenol, and BayK8644 increased cardiomyocyte contractile forces by 19.31%, 9.75%, and 23.81%, respectively. Verapamil decreased the contractile force by 48.06%. In summary, we monitored bending movement with cantilever sensors and concluded that cardiomyocyte contractile force changes in response to various drug treatments.